The Predictive Value of Endometrial Thickness in Endometrial Pathologies in Premenopausal Women with Abnormal Uterine Bleeding: - Darabi, Roksana; Mohit, Mitra; Mohammadkhani, Hengameh; Mohammadyari, Fathemeh; Yadollah-Damavandi, Soheila (Galen Medical Journal, 2013)
Abstract Background: Abnormal uterine bleeding (AUB) is one of the most common complains in women of any age seeking gynecologic health care and needs early diagnosis and proper management due to its impacts on the quality of life. This study was conducted to investigate the cut-off value of endometrial thickness (ET) by trans-vaginal ultra-sonography (TVUS) and evaluate its accuracy in the diagnosis of the endometrial abnormalities in premenopausal women with AUB. Materials and Methods: In this descriptive Â study, 64 married women between 35-50 years old were evaluated due to AUB during 2011-2012; TVUS and fractional curettage were done. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of the ET were calculated in different cut-off values. Results: The pathological evaluations of the biopsies were normal in 37 (57.8%) patients and were abnormal in 27 (42.2%) patients, 19 endometrial polyps, 6 hyperplastic lesions and 2 endometrial cancers. ET=4 mm had 100% sensitivity, 100% NPV, 10% specificity and 28% PPV in the detection of endometrial abnormalities. ET<10 mm had a proper sensitivity (67%-100%) and NPV (78.6%-100%) but specificity was low (%10-%44). ET=10 mm with sensitivity=63%, specificity=60%, NPV=65.8% and PPV=48.2% was introduced as the cut-off point with the best area under curve (LR+=2.22 LR- =0.77). Conclusion: Although an ET<10 mm was less likely to be associated with an endometrial abnormality, the low PPV of ET and low area under ROC curve shows sonography has high false positivity in premenopausal women. ETâ‰¤4 mm was more reliable and could reduce unnecessary biopsies.